Doing research in political science : an introduction to comparative methods and statistics - Pennings, Paul. ; Keman, Hans. ; Kleinnijenhuis, J. (SAGE Publications, 2020)
This thoroughly revised edition of the popular textbook offers an accessible but comprehensive introduction to comparative research methods and statistics for students of political science. Clearly organized around three parts, the text introduces the main theories and methodologies used in the discipline. Part 1 frames the comparative approach within the methodological framework of the political and social sciences. Part 2 introduces basic descriptive and inferential statistical methods as well as more advanced multivariate methods used in quantitative political analysis. Part 3 applies the methods and techniques of Parts 1 and 2 to research questions drawn from contemporary themes and issues in political science.gpt. 1.|tComparative methodology --|g1.|tComparative methodology and statistics in political science --|g2.|tThe comparative approach : theory and method --|g3.|tMeaning and use of the comparative method : research design --|gpt. 2.|tStatistics in political science --|g4.|tConcepts, cases, data and measurement --|g5.|tExplorative and descriptive statistics --|g6.|tMultivariate analysis and causal inference --|gpt. 3.|tDoing political research --|g7.|tHow problems arise --|g8.|tHow decisions are made --|g9.|tHow problems are solved.